2019
DOI: 10.14689/ejer.2019.79.1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gender Roles in Primary School (1st to 4th Grade) Turkish Textbooks

Abstract: Purpose: Textbooks can directly or indirectly affect gender stereotypes. In this study, text characters and pictures of textbooks were examined to find out how the messages were given about gender. This study examined text characters and the pictures in the primary school Turkish textbooks respectively in terms of Bem's Sex-Role Inventory and gender stereotypes. Research Methods: This paper explored the roles of text characters and pictures in the primary school Turkish textbooks through document analysis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
1
3
0
1
Order By: Relevance
“…This finding lends credence to Blumberg's (2008), Arslan Ozer, Karatas, and Ergun's (2019), and Parkin and Mackenzie's (2017) studies in which science textbooks tend to be in favour of men. The stark overrepresentation of males as opposed to the paucity of the representation of women, regardless of whether it is consciously or unconsciously done, may generate an impression for students that biological science is androcentric when students interact with the biology textbooks in their classroom.…”
Section: Discussionsupporting
confidence: 70%
“…This finding lends credence to Blumberg's (2008), Arslan Ozer, Karatas, and Ergun's (2019), and Parkin and Mackenzie's (2017) studies in which science textbooks tend to be in favour of men. The stark overrepresentation of males as opposed to the paucity of the representation of women, regardless of whether it is consciously or unconsciously done, may generate an impression for students that biological science is androcentric when students interact with the biology textbooks in their classroom.…”
Section: Discussionsupporting
confidence: 70%
“…Where textbooks act as one of the primary sources of knowledge holds a central role in developing the learners' characters [10]- [12], including the internalisations of values and communal norms [1]. Yet researchers have found that binary oppositions are still prevalent even in the educational textbook [1], [2], [4], [5], [8] - [22]. It has been revealed that textbooks still depicted patriarchal gender binaries.…”
Section: Introductionmentioning
confidence: 99%
“…deconstruct the binaries as identified by [12] and [23]. Some researches found that ELT textbook encompasses the gender binaries and represent equal representation among the gender [1], [2], [8]. In Indonesia, studies related to gender stereotyping in ELT textbook for elementary school [9], junior, high school [11], and senior high school [4] and they mostly revealed that the woman is still under-represented in ELT textbook.…”
Section: Introductionmentioning
confidence: 99%
“…En sociedades patriarcales, los discursos -que nunca son neutrales, sino que están cargados de ideología-legitiman las desigualdades de género. Dentro de la escuela, además de en las propias intervenciones del profesorado, estos se encuentran presentes en el recurso didáctico empleado por excelencia para la transmisión de información: los manuales escolares (Arslan et al, 2019). A través de ellos, el alumnado recibe un cierto sistema de creencias que legitiman el estatus quo y el orden social de los grupos hegemónicos que ostentan el poder, hecho que suele pasar desapercibido, mucho más a edades tempranas, en las que el estudiantado asume los contenidos como verdaderos, universales e incuestionables (Brugeilles, 2009).…”
Section: Antecedentesunclassified